2010
DOI: 10.1080/19404476.2010.11462069
|View full text |Cite
|
Sign up to set email alerts
|

“I Wish I Had Known the Truth Sooner”: Middle School Teacher Candidates’ Sexuality Education Experiences

Abstract: While many general education classroom teachers encounter issues of sexuality in the middle school classroom, few teacher candidates feel prepared to address them. One source of information for teacher candidates is the role modeling provided by their own teachers when they were elementary and secondary students. In this study, 107 teacher candidates enrolled in a middle level preparation course completed five stem sentences describing their experience of being educated about sexuality when they were younger. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 16 publications
0
9
0
2
Order By: Relevance
“…What little data exist focuses primarily on sexuality education teachers' ideas about the youth they work with and preservice teachers understanding of sexuality and education (Klein & Breck, 2010;Rodriguez, Young, Renfro, Asencio, & Haffner, 1996;Summerfield, 2001).…”
Section: Sex Education Teachersmentioning
confidence: 99%
See 1 more Smart Citation
“…What little data exist focuses primarily on sexuality education teachers' ideas about the youth they work with and preservice teachers understanding of sexuality and education (Klein & Breck, 2010;Rodriguez, Young, Renfro, Asencio, & Haffner, 1996;Summerfield, 2001).…”
Section: Sex Education Teachersmentioning
confidence: 99%
“…Data show that teachers feel unprepared to provide sexuality education and often report little to no formal training on the topic (Cohen, Byers, Sears, & Weaver, 2004;Klein & Breck, 2010;Walters & Hayes, 2007). Although teacher preparation in sexuality education varies from state to state, in a study undertaken by Sexuality Information and Education Council of the United States (Rodriguez et al, 1996), researchers found that none of the 251 teacher education programs sampled provided formal classes or training in sexuality education to preservice teachers.…”
Section: Sex Education Teachersmentioning
confidence: 99%
“…childhood (see also Klein and Breck 2010). During their four-year BEd (Primary) degree at Time 2, only two student-teachers, both male, reported being exposed to more contemporary and interactive teaching approaches, such as discussion, discovery, or roleplay, with the other four student-teachers learning almost nothing that would change their teaching practices or intentions for this course area from traditional pedagogies such as lecture-recitation, modelling and demonstration.…”
Section: Sex Education 285mentioning
confidence: 99%
“…Another [M3] said, 'We are supposed to be teaching students to become life-long learners so we have to prepare them, but I wouldn't feel comfortable on my own to teach this'. Despite these insights of metacognitive knowledge, the educational trajectories of these student-teachers, at least regarding puberty/sexuality education, are those of replicating the educational status quo (see also Goldman 2010; Klein and Breck 2010;UNESCO 2009).…”
Section: Sex Education 285mentioning
confidence: 99%
See 1 more Smart Citation